PENGEMBANGAN PENUNTUN PRAKTIKUM FISIKA BERBASIS INKUIRI UNTUK CALON GURU SEKOLAH DASAR - Osang Suari, Ani; Hairida, Hairida; Irfan Izudin , Muhammad; Pranata, Rio (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
21st-century skills are essential competencies that students need to have and can be facilitated through inquiry-based learning, however, some of the practicum guides used are not sufficient to support this, they are still limited to proof of concept alone and have not facilitated the development of 21st-century skills in the practicum learning process, so it is necessary to develop an inquiry-based physics practicum guide. This study aims to develop and validate an inquiry-based physics practicum guide in the S1 PGSD study program, FKIP UNTAN. This study uses a Research and Development (R&D) approach with a modification of the ADDIE development model which includes the stages of Analysis, Design, and Development. The subjects in this study were two physics learning experts. The practicum guide was validated using a questionnaire in this study. The results of validation by two physics learning experts on the aspects of material, language, and presentation showed an average score of 0.92; 0.94; and 0.92, respectively, with the category of